The Implementation of Communicative Language Teaching Approach in Selected Secondary School: Nepalese Teachers' Perspective - Tiwari, Trilok Datt (Utamax : Journal of Ultimate Research and Trends in Education, 2021)
Throughout the history of second/foreign language teaching, several methods and approaches have been developed. Among them, Communicative Language Teaching (CLT) has been a popularly practiced method in the modern context as there are a large number of teachers around the world who claim that they are using CLT. However, previous studies revealed that there is a discrepancy between their claim and their performance in real practice. Therefore, this research aims at exploring the perceptions of Secondary-level English teachers towards the CLT method along with the activities they use and the challenges they encounter. Using a qualitative descriptive inquiry, a close-ended questionnaire was sent via e-mail to the four purposively selected teachers teaching in public Secondary-schools in Kanchanpur, Nepal. In addition, an interview protocol was used with Four of the teachers. The findings of the study revealed that the teachers had positive perceptions towards the CLT method. However, the present study also highlighted that the teachers did not involve many communicative activities which are essentially needed for the successful implementation of the method. This study further exposed that the participants seem encountered several challenges while implementing the CLT method which is quite similar to the challenges faced by the teachers in the region. These results emphasized that the teachers should try to contextualize and maximize communicative activities amidst the challenges.